Eucalyptus oil to mitigate heat stress in broilers - Petrolli,Tiago Goulart (2019)
ABSTRACT The objective of this study was to evaluate performance, hematological parameters, leukocyte counts, and respiratory microbiota of broilers under heat stress receiving eucalyptus oil supplementation. Cobb broilers (n = 1200) were randomly distributed on the first day of life in a factorial arrangement with additional treatment (2 × 2 + 1) with two periods of oil administration via drinking water (daily, from 18 to 35 days of life) and two periods of oil administration via spray (daily, from 18 to 35 days of age) plus a control treatment, consisting of twelve replications, with 20 animals each. The birds were kept in a controlled environment with constant temperature at 32 °C to induce heat stress by infrared heaters. Eucalyptus oil was supplied by drinking water (1 L of oil to 4000 L of water) or by spray applications with a pump (1 L of oil to 200 L of water). Bird weight was recorded at 42 days of age, along with remaining feed, to determine weight gain, feed intake, and feed conversion. In addition, one blood sample from each bird repetition was collected for hematological and leucocytic evaluation. To assess respiratory microbiota, a tracheal flushing was performed for bacteria counts. There was no difference in performance, hematological parameters, and leukocyte counts, except hematocrit, which was lower in birds that received eucalyptus oil after 18 days of age. No significant differences were observed in the respiratory microbiota comparing oil-treated and -untreated groups. Although it was not possible to verify statistical difference, the birds that received eucalyptus oil via spray plus spray from 18 days old showed lower bacterial counts and absence of isolation of Gram negatives, while the control group was the one with the highest number of Gram negatives. Therefore, eucalyptus oil can be used for heat-stressed broilers without impairing their development.